Examining Economic Hardship Resulting from Fuel Subsidy Removal in Nigeria: A Critical Reflection through the Lens of Karl Jaspers' Boundary Situations - Tughhemba, Terfa Nicholas; Washima, Akputu Innocent (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2024)
Existentialism is a philosophical movement that recognises the ineptitudes of life and attempts to solve them by encouraging a deep reflection upon human existence in order to create an authentic individual in a hollow and absurd life. Since the removal of fuel subsidies by President Bola Tinubu, Nigerians have experienced economic hardship due to the astronomical rise in goods and services. This paper examined the tales of economic hardship occasioned by the removal of fuel subsidies in Nigeria with a view to re-echoing Karl Jasper’s concept of “boundary situations." We derived data from both primary and secondary sources. These include books, journals, periodicals, and the Internet. The historical method presented a brief historical overview of subsidy removal in Nigeria. The expository method provided Karl Jaspers’ existential thoughts in detail, with a specific focus on his notion of boundary situations, while the analytical method established the relevance of Karl Jaspers’ thought to the current condition that fuel subsidy removal has brought on Nigerians. The study found that fuel subsidy removal freed up financial resources for other sectors of the economy. At the same time, it has increased inflation, insecurity, etc. Thus, the paper concluded that in the unique and historical experience of boundary situations, it is up to each individual to realise the proper moral attitudes or virtues to adopt, thereby ensuring individual authenticity. It is recommended that the government commit more funds to providing palliatives and make policies to boost economic growth and stability.